The great escape - Dale, Jenny; Reid, Mick; Rowe, Michael (London : MacMillan, 1998)
Neil investigates when a beagle escapes from the King Street Kennels and her puppies are also missing.
5.7
3-6
Keywords: Dogs -- Fiction; King Street Kennels (Imaginary organization) -- Fiction